Investigation of the Effects of Social Capital on Information/Knowledge-Sharing Behavior that Drives Gen Z Purchase Intentions through Social Commerce - Endy Gunanto Marsasi; Sarah Barqiah; Yenni Kurnia Gusti (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
This study investigates the impact of social capital theory in social networks on consumer decision-making, highlighting the importance of product features and peer preferences. It identifies a research gap in understanding the effects of structural, relational, and cognitive capital, emphasizing the need for further exploration. The study also examines the relationship between information sharing and purchase intention, addressing a previously neglected area. Additionally, it explores how age and gender, influence consumer characteristics. The empirical data collected from 223 respondents who buy consumer goods through social media as part of the millennial generation through an online survey is analyzed using SEM. Results indicate that structural, cognitive, and relational capital influence the exchange of information. The behavior of sharing information indicates that the more people who provide positive information about a consumer goods product, the higher the intention to buy, it is anticipated that the company will increase its promotion on Twitter and Instagram. This is due to the fact that many consumers use the platform in their daily lives and consumers desire to always be willing to share the information they possess. Moreover, younger women are more inclined to share information based on their age and gender characteristics.